Morphologic patterns and treatment of transplant glomerulopathy: A retrospective analysis. Issue 4 (21st February 2017) - Abreu, Rui; Carvalho, Fernanda; Viana, Helena; Mesquita, Isabel; Possante, Marília; Aires, Inês; Caeiro, Fernando; Silva, Cecília; Cotovio, Patrícia; Ferreira, Aníbal; Remédio, Francisco; Nolasco, Fernando
Abstract: Transplant glomerulopathy is mainly due to chronic antibody‐mediated rejection and actually represents a major cause of long‐term allograft failure. The lack of effective treatment remains a serious problem in transplantation. A retrospective and uni‐center study was performed in 48 kidney allograft recipients with transplant glomerulopathy between January 2010 and December 2015. Median time for diagnosis was 7.1 (3.6‐11.8) years post‐transplant. Light microscopy showed severity of transplant glomerulopathy in the majority of patients (cg1=10.4%; cg2=20.8%; cg3=68.8%). Moderate microvascular inflammation was present in 56.3% (g+ptc≥2), and almost half of recipients (51.1%) were C4d positive in immunofluorescence. Female gender ( P =.001), age ( P =.043), renal dysfunction ( P =.002), acute rejection episodes ( P =.026), and anti‐HLA class II antibodies ( P =.004) were associated with kidney allograft failure. Treatment of transplant glomerulopathy was performed in 67.6% of patients. The histologic and laboratory features that led to a therapeutic intervention were score ptc ( P =.021), C4d ( P =.03), and the presence of anti‐HLA antibodies ( P =.029), whereas score ah ( P =.005) was associated with conservative measure. The overall cumulative kidney allograft survival at 10 years was 75%. Treatment of transplant glomerulopathy was ineffective to improve long‐term kidney allograft survival.